Teaching Strategies for Bangklung Art in School Extracurricular Activities at SDN 3 Cisero, Garut Regency - Salma Nurul Maulida; Nanang Supriatna; Urfan Saniylabdhawega Ridhwan (GoAcademica Research & Publishing, 2026)
This study examines teaching strategies for Bangklung art in extracurricular activities at SDN 3 Cisero, Garut Regency, in response to the declining interest of younger generations in traditional arts. Using a qualitative case study approach, data were collected through observation, interviews, and documentation, and analyzed using an interactive model of data reduction, data display, and conclusion drawing. The findings reveal that Bangklung learning is structured through an integrated strategy combining demonstration-based instruction, structured repetition, and collaborative ensemble practice. These strategies are implemented through routine practice sessions, gradual instrumental familiarization, and performance-oriented activities. The instructor plays a central role not only as a technical guide but also as a cultural facilitator who fosters discipline, cooperation, and cultural awareness among students. The study indicates that practice-oriented and socially interactive learning strategies contribute to students’ engagement and appreciation of traditional arts while supporting character development. The findings also highlight the role of extracurricular activities as a bridge between community-based cultural practices and formal education. Despite challenges such as limited instruments and students’ unfamiliarity with traditional repertoire, the program demonstrates strong potential as a model for cultural preservation through school-based music education.